The human side of digital business transformation - Lardi, Kamales (Hoboken, NJ Wiley, 2023)
The Human Side of Digital Business Transformation provides personal stories and anecdotes from the people who have successfully bridged the analog-to-digital divide. It also includes best practices and learnings your firm can leverage to accelerate your own transformation journey. An essential strategic playbook for managers, executives, and other business leaders, this book also belongs in the libraries of technology professionals, as well as consultants and other professionals who serve companies of all sizes
Keywords: Quản trị kinh doanh